A patient with macrodystrophia lipomatosa bilaterally affecting the entire upper extremity: reporting of a rare case and literature review. Issue 1 (1st January 2021) - Baba, Kyoko; Kashiwagi, Shinya; Nemoto, Mitsuru; Takeda, Akira; Fukumoto, Keizo; Uchinuma, Eiju
Abstract: The patient, a 58-year-old Asian female, had the progressive, bilateral overgrowth of the entire upper extremity since her childhood and has undergone debulking surgery twice in her country. However, overgrowth progressed after surgery. The patient was diagnosed with Macrodystrophia lipomatosa (MDL) by physical and imaging findings in our departments.